2023
DOI: 10.1111/cpr.13411
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA AC018926.2 regulates palmitic acid exposure‐compromised osteogenic potential of periodontal ligament stem cells via the ITGA2/FAK/AKT pathway

Abstract: Although obesity has been proposed as a risk factor for periodontitis, the influence of excessive fat accumulation on the development of periodontitis and periodontal recovery from disease remains largely unknown. This study investigated the cellular response of periodontal ligament stem cells (PDLSCs) to elevated levels of a specific fatty acid, namely, palmitic acid (PA). The mechanism by which PA exposure compromises the osteogenic potential of cells was also explored. It was found that exposure of PDLSCs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Since the regulatory roles of lncRNAs are associated with their subcellular localization, 30 we performed the FISH and subcellular fractionation assays illustrating that LncTUG1 was mainly distributed in the nuclear fraction (Figure 2A,B ), which suggested that LncTUG1 might regulate the transcription of targeted genes. 33 Based on this finding, we further investigated the downstream gene targeted by LncTUG1 during stress‐induced cementocyte mineralization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the regulatory roles of lncRNAs are associated with their subcellular localization, 30 we performed the FISH and subcellular fractionation assays illustrating that LncTUG1 was mainly distributed in the nuclear fraction (Figure 2A,B ), which suggested that LncTUG1 might regulate the transcription of targeted genes. 33 Based on this finding, we further investigated the downstream gene targeted by LncTUG1 during stress‐induced cementocyte mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…An orthodontic closed coil spring (Grikin Advanced Materials, Beijing, China) was inserted between the maxillary left first molar (M1) and the incisor to achieve orthodontic molar movement with 0 g (Control group) and 25 g (Stress group). Stress was also combined with daily intraperitoneal injection of a TLR4‐specific agonist Lipopolysaccharide (LPS) (2 mg/kg, L2630, Millipore, Sigma‐Aldrich, St. Louis, MO, USA) 30 or with intraperitoneal injection of an SphK1 activator (0.05 mg/kg, K6PC‐5, Selleck, Beijing, China), 31 , 32 which were divided as Stress + LPS group and Stress + K6PC‐5 group, respectively. After 14 days, all experimental rats were euthanized by an overdose of pentobarbital and alveolar bone blocks that included M1 were harvested for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has found that the miRNA-140-5p expression decreased during osteogenic differentiation process of BMSCs, and BMSCs osteogenic differentiation is promoted by miRNA-140-5p down-regulation through targeting the Wnt l signal pathway [7] , however, the relative mechanism about miRNA-140-5p low expression in this process is still unclear. LncRNAs, as a miRNA molecular sponge, LncRNAs have increasingly been studied in relation to osteogenic differentiation [24][25][26][27][28] . The predicted results of Star base Database indicated that lncRNA-H19 may target the miRNA-140-5p.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ability of pancreatic β-cells to resist oxidative stress is relatively weak, and oxidative stress induced by being in a high-fat state inevitably causes damage to the function and number of β-cells. Palmitic acid (PA), a saturated fatty acid [ 8 , 9 ] widely present in palm, vegetable, and catalpa oils, is the major component obtained from the daily diet that accumulates in the body, resulting in lipotoxicity of pancreatic β-cells.…”
Section: Introductionmentioning
confidence: 99%